Tiger economies under threat : a comparative analysis of Malaysia's industrial prospects and policy options - Yusuf, Shahid, 1949- (World Bank e-Library., 2009)
Southeast Asian tiger economies feel threatened by competition from other countries and worry that their growth momentum might be flagging. Even though their growth rates are above the average for the world and for developing countries, they fall short of yesterday's economic performance. The underlying worry is that they presage the beginning of a downward trend, the harbingers of which are lower rates of investment, persistently low rates of total factor productivity and low levels of innovativeness. The South East Asian tigers' worries motivate three questions: First, are the tigers rightly.